If f(x)=x(x-1)(x+1), what is the product of the nonzero real numbers x such that f(x)=x
1. f(1/x) + 2f(x) = x for all nonzero real x... therefore, the same should hold true if you substitute 1/x for x: 2. f(x) + 2f(1/x) = 1/x Multiply the original equation through by 2: 3. 2f(1/x) + 4f(x) = 2x Now substract equation #2 from equation #3, and solve for f(x): ( 2f(1/x) + 4f(x) ) - ( f(x) + 2f(1/x) ) = 2x - 1/x 2f(1/x) - 2f(1/x) + 4f(x) - f(x) = 2x^2/x - 1/x 3f(x) = (2x^2 - 1)/x f(x) = (2x^2 - 1)/3x
Content will be erased after question is completed.
Enter the email address associated with your account, and we will email you a link to reset your password.
Forgot your password?